Chumbo e cádmio no sangue e estado nutricional de crianças, Bahia, Brasil Lead and cadmium in the blood and their relation to the nutritional status of children in Santo Amaro, Bahia, Brazil - Fernando Martins Carvalho; Annibal Muniz Silvany Neto; Maria Engrácia Chaves Lima; Tânia Mascarenhas Tavares; Maria da Graça Andrade Azaro; Gilca Maria Cardoso Quaglia (Universidade de São Paulo, 1987)
Num estudo de prevalência foi estudada a relação entre níveis de chumbo (PbS) e de cádmio no sangue (CdS) e o estado nutricional de crianças de 1 a 9 anos de idade, residentes a menos de 900 metros de uma fundição primária de chumbo, situada em Santo Amaro da Purificação, Bahia, Brasil. Em 555 crianças o nível médio (média ± s) de PbS foi de 2,84 ±1,20 µmol/1. Em 396 crianças, o nível médio de CdS (geométrico) foi de 0,087 µmol/1, com desvio padrão de 2,5. Os níveis de PbS e de CdS estavam extremamente elevados, mas não variaram significantemente entre subgrupos de crianças de diferentes estados nutricionais. Análises de regressão múltipla não mostraram associações estatisticamente significantes entre os níveis de PbS ou logCdS 1 malnutrição, medida através da relação peso/altura, mantidos constantes os efeitos de idade, sexo, grupo racial, hábito de geofagia, distância do domicílio da criança à fundição, ser filho de trabalhador da fundição, renda familiar, balanço de ferro do organismo e infestação ancilostomótica severa. A distância do domicílio da criança à fundição foi a variável que se mostrou mais fortemente associada à variação dos níveis de PbS ou de logCdS. O peso ou a altura de crianças com baixos níveis de chumbo no sangue (iguais ou inferiores a 1,68 µmol/1) não estavam significantemente associados com os níveis de PbS, mas mostraram elevada correlação com a idade dos indivíduos. The levels of lead in blood (PbB) and of cadmium in blood (CdB) were related to nutritional status, in the context of a prevalence study, carried out in a population of 1 to 9 year-old children, living at less than 900 meters from a primary lead smelter in Santo Amaro City, State of Bahia, Brazil. Among 555 children, the arithmetical mean and standard deviation of PbB levels was 2.84 ± 1.20 (µmol/1. More than seventy-five per cent of the children presented PbB higher than 1,68 µmol/1 (or 35 µg/100 ml), which is usually taken as a safe reference level. Among 396 children, the geometrical mean of CdB levels was 0.087 µmol/1 (standard deviation of 2.5). Ninety-six per cent of these children presented CdB levels higher than 0.0089 µmol/1 (or 1.0 µg/1), which is usually taken as a reference level. PbB and CdB levels did not vary significantly among subgroups of children of different nutritional status. Multiple regression analyses did not show statistically significant associations between PbB or logCdB levels and malnutrition, as measured by the wasting (weight/length) index, the effects of the following variables remaining constant: age, sex, racial group, pica, distance from child's home to smelter, being a child of a leadworker, family income, iron status and severe hookworm infestation. The distance from child's home to smelter was the variable which was most strongly associated with the variation in PbB or in logCdB levels. The weight or the height of children with low PbB (equal or less then 1.68 µmol/1) were not significantly associated with PbB levels, but showed strong correlations with child's age. These results disagree with those from a recent study carried out in a large sample of American children, which reported strong associations between child's height or weight and the level in blood for children with PbB below 1.68 µmol/1.